Preparation and Characterization of a New Polymer/Pharmaceutical-Based Composite. Part I: Meloxicam - Rabagliati-Canessa, F; Cardenas-Sankan, G; Orihuela-Diaz, P; Galvez-Manriquez, D; Zapata-Ramirez, P; Canales-Arévalo, D (Springer Verlag, 2014)
Composites of low-density polyethylene (LDPE), poly(ethylene-co-vinyl acetate) (EVA), poly(ethylene-co-octadecene), and an LDPE/EVA blend were prepared with different amounts of meloxicam (1, 3 and 5 wt %) by the melt blending process. Meloxicam was homogenously dispersed in polymer matrices. The polymer–meloxicam composites showed thermal behavior and thermal characteristics similar to those of the original polymers. Meloxicam release from the composites was examined in vitro for 50 days. The composites were incubated in phosphate-buffered solution and meloxicam concentration was determined by high-performance liquid chromatography. The prolonged release of the drug indicates that meloxicam-loaded plastic rings offer potential for control of reproduction and chronic inflammatory conditions. © 2014, Springer-Verlag Berlin Heidelberg.